RANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMAAN PESANAN PADA PERUSAHAAN MAKE TO ORDER DENGAN MODEL MATEMATIKA OPTIMASI: RANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMAAN PESANAN PADA PERUSAHAAN MAKE TO ORDER DENGAN MODEL MATEMATIKA OPTIMASI - Indro Prakoso; Kholida Hanim (JURNAL REKAYASA SISTEM INDUSTRI, 2019)
Manufacturing companies engaged in the system of making orders are now starting to develop with increasingly diverse needs, and the business of making agricultural and food processing machinery is no exception. UD. rekayasa Wangdi W produced the machine processing manufacturing companies engaged in the make to order system are now starting to develop rapidly along with increasingly diverse needs, and the business of making agricultural and food product processing machines is no exception. UD. Wangdi W Engineering is a Make To Order (MTO) manufacturer of processing machines which currently does not consider resource capacity and order due to date as a reference for receiving orders. Even though accepting all orders does not necessarily provide maximum benefits. To help solve these problems, a decision support system design for planning the acceptance of customer orders is carried out. The system is designed using a mathematical model that was developed and modified in linear programming. The model developed has an objective function of maximizing profits from orders received and applied in the system built. The system is designed and the Mathematical Model is processed using the branch and bound method. Based on experimentation with historical data, the results obtained are only 4 slicer and 10 spinner units with a maximum profit of Rp53,115,530.00 and order completion that does not exceed the due date. Order acceptance information is displayed in tabular form and machine scheduling information is displayed in Gantt chart format